2013
DOI: 10.3945/ajcn.112.034025
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fiber intake and risk of hormonal receptor–defined breast cancer in the European Prospective Investigation into Cancer and Nutrition study

Abstract: Diets rich in dietary fiber and, particularly, fiber from vegetables may be associated with a small reduction in risk of BC, independently of menopausal status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
70
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 78 publications
(80 citation statements)
references
References 46 publications
7
70
0
2
Order By: Relevance
“…Consistently, the NIH-AARP Diet and Health Study found that dietary fiber intake in the highest quintiles can lower postmenopausal breast cancer risk by 13% (RR=0.87; 95%CI: 0.77-0.98) (Park et al, 2009). Although our study findings were supported by two prospective studies, several other studies failed to establish that a diet with low dietary fiber has harmful effects towards breast cancer risk among postmenopausal women (Holmes et al, 2004;Giles et al, 2006;Cade et al, 2007;Suzuki et al, 2008;Wen et al, 2009;Shikany et al, 2011;Zaineddin et al, 2012;Ferrari et al, 2013).…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Consistently, the NIH-AARP Diet and Health Study found that dietary fiber intake in the highest quintiles can lower postmenopausal breast cancer risk by 13% (RR=0.87; 95%CI: 0.77-0.98) (Park et al, 2009). Although our study findings were supported by two prospective studies, several other studies failed to establish that a diet with low dietary fiber has harmful effects towards breast cancer risk among postmenopausal women (Holmes et al, 2004;Giles et al, 2006;Cade et al, 2007;Suzuki et al, 2008;Wen et al, 2009;Shikany et al, 2011;Zaineddin et al, 2012;Ferrari et al, 2013).…”
Section: Discussionsupporting
confidence: 54%
“…In the United Kingdom, a developed country, premenopausal women needs more than 30 g/day of dietary fiber to have the same protective effects (RR=0.48; 95%CI: 0.24-0.96) (Cade et al, 2007). However, three other prospective studies found that dietary fiber intake of 25 g per day at the highest quintiles were not able to reduce the risk of premenopausal breast cancer (Cho et al, 2003;Holmes et al, 2004;Ferrari et al, 2013). Much lower intake of dietary fiber at 16 g/day DOI:http://dx.doi.org/10.7314/APJCP.2014.15.14.5959 Dietary Carbohydrate, Fiber, Sugar and Breast Cancer Risk among premenopausal women in China, was found to have no significant association between dietary fiber intake and breast cancer risk exists (Wen et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All of these bioactive components have well known properties in the prevention of some types of cancers especially breast cancer. Dietary fiber is one of these protective compounds that ecological data as well as prospective and clinical studies are in agreement about its beneficial effects; recently, results from European Prospective Investigation into Cancer and Nutrition (EPIC) showed that diets rich in dietary fiber and, particularly, fiber from vegetables may be associated with a small reduction in risk of breast cancer (Ferrari et al, 2013). Meta-analysis of the previous evidences from prospective studies also confirms the protective role of dietary fiber against breast cancer .…”
Section: Discussionmentioning
confidence: 97%
“…, Christina C Dahm 21 , Kim Overvad 21 , Laure Dossus 22,23,24 , Agnès Fournier 22,23,24 , Laura Baglietto 25,26 , Renee Turzanski Fortner 6 , Rudolf Kaaks 6 , Antonia Trichopoulou 27 Breast cancer (BC) remains the highest incident cancer affecting women worldwide, with almost 1 670 000 cases registered in 2012. It is a major public health concern with mortality from BC accounting for over 522 000 deaths in 2012, including almost 198 000 deaths in Western countries and about 324 000 in less developed regions (1) .…”
mentioning
confidence: 99%